Pendampingan Hidroponik 55 untuk Tumbuh Kembang dengan Usaha Produksi Sayur Sehat dan Menjadi Tujuan Eco-Eduwisata di Cupak Tangah, Padang - Fitri Mailani; Donny Eros; Jauharry Jauharry; Mulyanti Roberto Muliantino (Warta Pengabdian Andalas, 2021)
The advantages of this hydroponic vegetable product are that it is free of chemical pesticides, the taste of vegetables is crunchy and sweet, clean, environmentally friendly, and affordable. However, the public's knowledge and understanding regarding hydroponic vegetables is still very little and not evenly distributed in all circles, so that marketing is only limited to certain groups. This service aims to assist and assist Hydroponics 55 partners in producing healthy vegetables and developing into an Eco-tourism area. This service activity is planned to last for 3 years (2021-2024). With the following activity plans: 1) designing a green-house in agricultural areas, 2) increasing online and offline promotion and education, 3) submitting a proposal for collaboration with restaurants, cafes, hospitals and supermarkets in the city of Padang, 4) developing Hydroponic 55 businesses, in processing healthy food derived from hydroponic vegetables, 5) developing agricultural areas into Eco-tourism areas. Activities that have been carried out this year include making educational posters and promoting hydroponic vegetables and distributing them through social media, conducting FGDs with stakeholders, inviting speakers regarding greenhouse preparation and providing knowledge dissemination related to marketing tricks and eco-tourism concepts and facilitating partners in develop business licenses in processing healthy food products. The results of this activity are in the form of educational and promotional posters, proposals for making green-houses, proposals for developing healthy food processing and proposals for developing eco-tourism areas.